Implementasi Bahan Ajar Kimia Terintegrasi Nilai Spiritual Dengan Model Pembelajaran Problem Based Learning (PBL) Berorientasi Kolaboratif Untuk Meningkatkan Hasil Belajar Siswa - Heppy Okmarisa; Ayi Darmana; Retno Dwi Suyanti (Jurnal Pendidikan Kimia (JPKim), 2016)
Abstract. This Study aims to determine: (1) is there a difference between the increas student learning outcomes are taught using chemistry teaching materials integrated spiritual with using chemistry teaching materials SMA/MA with Problem-Based Learning (PBL)  model oriented Collaborative. (2) whether are chemistry teaching materials integrated spiritual can effectively develop student’s spiritual. (3) whether  there is a relationship between spiritual values with improved learning outcomes. Sample in this study is two classes. Research instruments in the form of a multiple choice test of 25 item that valid and reliable (0,84), questionnaire and observation sheet are used measure the spiritual attitude. The data analysis using consist of Independent Sample T-test, Correlation and Regression of SPSS 21 for  windows with 0,05 significance level. The result of research and testing indicate : (1) Improving student learning outcomes are taught using chemistry teaching materials integrated spiritual higher that the results of learning by the chemistry teaching materials SMA/MA with Problem-Based Learning (PBL)  model oriented Collaborative (p = 0,000 < 0,05), the average value of the N-Gain experimental class 1 is 80 % and experimental class 2 is 66 %, (2) chemistry teaching materials are developed to grow spiritual values in students, (3) there is a relationship between the spiritual value to student learning outcomes. Keyword: learning, spiritual values, teaching materials, problem-based learning-oriented collaborative